Sobre equações integrais de evolução e aplicações - Santos, Jucileide dos (2019)
Motivated by the huge success of the applications of the Evolutionary Integral Equations in many areas of engineering and the fact that the literature has several open problems, in this work we aimed to study the theory involving abstract Volterra equations as well as issues related to a Cauchy fractional problem of order 0<α<1. In this last one we try to answer some questions about the global well-posedness and self-similarity of the solutions.